Study of the Restricted Non-Rigid Group of Tetramethyl Tungsten Hybrid - IRANMANESH, A.; MEMARZADEH, S. (Asian Journal of Chemistry, 2010)
A simple method is described for calculation of character tables for the symmetry group of molecules consisting of a number of CH3 group attached to a rigid framework. The restricted non-rigid group of this molecule is seen to be a group of order 324 and it has a point-group symmetry C2v. We prove that it is a group with 33 conjugacy classes and also computed the character tables of this group.